From Celebrity to Speculator – Retail Investor Experiences with Controversial Endorsements and Stock Price Dynamics in Indonesia’s Emerging Market - Sandopart, Dewa Putu Yohanes Agata L. (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Celebrity endorsements and financial influencers have become a significant phenomenon in the Indonesian capital market, coinciding with a rise in stock manipulation cases driven by public figure recommendations. Regulatory authorities have documented numerous alleged capital market violations, including pump-and-dump schemes involving influencers. This study aims to explore in depth how retail investors experience and respond to controversial endorsements, and how these dynamics shape their perceptions of stock prices. Employing a qualitative approach with an instrumental case study design, the research involved interviews with 25 retail investors in Jakarta, Surabaya, and Medan who had invested in stocks promoted by endorsers. The findings identify three experiential patterns: FOMO-driven herding triggered by endorser authority, cognitive dissonance following losses attributable to recommendations, and resilience signaling as a self-defense mechanism. This study contributes by integrating source credibility perspectives with behavioral finance and offers policy implications for capital market regulators in managing influencer activity.